Self-Efficacy and Academic Cheating in Nursing Faculty Students - Mendrofa, Clarita Eka Putri; Novalinda, Dinda Rensi; Yuniar, Prista; Hutapea, Adventina; Tahulending, Peggy Sara (Universitas Prima Indonesia, 2024)
Several studies have found that the types of academic fraud that often occur are cheating, plagiarism, stealing exam materials, and handing over other people's assignments on their behalf. One of the reasons that causes academic cheating to occur is disbelief in one's capabilities which is called self-efficacy. Previous research has shown that low self-efficacy will give up faster and avoid difficulties because they are not sure of their abilities. Cheating behavior in the nursing profession is very bad because it will have a bad effect on patients like medication errors. Therefore, the purpose of this research was to determine the relationship between self-efficacy and academic cheating in nursing students. The research design used descriptive correlational. The sample in this study was nursing students at the University of Western Indonesia with a total of 183 respondents. The sampling technique used simple random sampling because the population was homogenous. Data was collected online by Google Forms. The data were analyzed using the chi-square test. It was found that the majority of self-efficacy was in the moderate category of 123 (67.2%), and academic cheating was in the low category of 165 (90.2%). The Chi-Square test showed a p-value of 0.002. There is a relationship between self-efficacy and academic cheating in nursing students. High self-efficacy will create a calm feeling to face difficult tasks, increase optimism, and reduce anxiety. Recommendations for nursing educational institutions can motivate students and modify learning methods so that students have the confidence not to commit academic fraud.